(3OjhGf GHf GdaGQVs - (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s
(3ChdgG (B:s
(3bGd Ydi SHW GdTjN GHf GdaGQV fXQJ aj fSN ef OjhGf TjNfG bOS Gddg SQg aQCjJ GdfSGN LgdhG HYV cdGeg heG YQahg, hGTJHg Ydjge TF ef LfGSg aUMahg s
(3BNQgG (B:s
(3OGQ GdSdGe EdjgG bO hUdJ EPG ef SHd CHhGH EjeGfj hESdGej jGQHfG CQfj CfXQ Edjg HgG YfO GdbOhe hYGedfj HEcQGe s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B216s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B171 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B767s
(3eUOQ GbJfGA GdCUd (B:s
(3EeHQhRjGfG (B(83) s
Keywords: (3GdCOHs